Analysis Financial Reports in Financial Prediction Distress with Method Grover and Springate on LQ45 Indexed Companies on BEI 2019 - 2022 - Safitri, Eka; Cloudya, Afifah; Mujanah, Siti; Fianto, Achmad Yanu Alif (International Journal of Economics (IJEC), 2025)
Analysis of the influence of financial distress and financial ratios with the Grover and Springate method is used to conduct a thorough examination of financial performance periodically over a certain period of time. so the purpose of this study is to determine how healthy a company is in the technology sector by analyzing factors that affect financial distress through financial ratios and the formula equation of the grover and Springate method. The results of this study are that the use of the GorgonL.V or S-SCORE method is a consistent method in predicting financial distress in companies, namely by approaching sales and total assets. by conducting financial distress predictions, companies can find out and prove the existence of factors that cause companies to go bankrupt. By increasing sales and proper management of total assets, companies can make high profits